Transport properties of CO2 and CH4 in hollow fiber membrane contactor for the recovery of biogas from anaerobic membrane bioreactor effluent - Rongwong, Wichitpan (2018)
A significant amount of methane (CH4) produced from anaerobic digestions of wastewater is dissolved in liquid effluent and discharged. The recovery of dissolved CH4 is therefore essential in ensuring an enhanced energy production of the anaerobic processes, and minimizing environmental impacts of the greenhouse gas. In this work, a membrane contactor is employed as a mass transfer equipment for the CH4 recovery. A mathematical model considering simultaneous desorption of CH4 and carbon dioxide (CO2) is developed using a resistance-in-series model to calculate the overall mass transfer coefficients. The simulations were validated with experimental results obtained using an in-house fabricated hollow fiber membrane as well as a real effluent from Anaerobic Membrane Bioreactor (AnMBR) and synthetic effluent made of water saturated with biogas. Results showed that the CO2 fluxes were higher than those of CH4 fluxes due to its higher concentration in liquid phase. A decrease of liquid phase mass transfer resistance by an increase in liquid velocity significantly enhanced both CH4 and CO2 fluxes. While, an increase in gas velocity slightly affected the CH4 flux but enhanced the CO2 flux considerably. It was also found that the CO2 desorption increased the CH4 recovery rate. The desorbed CO2 helped to increase the mass transfer driving force by reducing the partial pressure of CH4 in the gas side, and enhancing the gas phase mass transfer coefficient to facilitate CH4 desorption. The increase of liquid velocity increased mole fraction of CH4 in the gas outlet but decreased the rate of CH4 recovery. On the other hand, applying vacuum conditions to decrease gas pressure enhanced the rate of CH4 recovery but lower the CH4 mole fraction in the product gas.